Adjustment Dynamics of Bilateral Trade Flows: Theory and Evidence - Benjamin Jung (Swiss Journal of Economics and Statistics, 2009)
In this paper, I introduce a trade-promoting "invisible asset" into the standard Krugman (1980) model of international trade. It can be interpreted as trust that accumulates as an externality in proportion to successful international transactions. I use this framework to theoretically derive a dynamic gravity equation and to discuss adjustment dynamics. I provide new evidence on adjustment rates of bilateral trade flows. On average, 23% of the gap to the steady-state trade flow are closed each year. However, dynamic regressions yield long-run trade policy effects which are comparable to static estimates.
Keywords: F14; F15; 330; International bilateral trade; Gravity model; Trust; Dynamic panel data